THE RELATIONSHIPS LEARNING MOTIVATION AND ACADEMIC ACHIEVEMENT OF STUDENTS IN CLASSXI TKR SMK KARSA MULYA PALANGKA RAYA IN ACADEMIC YEAR 2015/2016 - Reynaldy; Vontas A. Nahan (Jurusan Pendidikan Teknologi Dan Kejuruan, 2017)
At the research, it was found a lot of students who lack in motivation to learn. Similarly, discovered at SMK Karsa Mulya Palangkaraya including this school has the students' achievement motivation which was substandard. Based on this background, the authors conducted research that aims to determine connected learning motivation and student achievement in vocational school of Karsa Mulya Palangkaraya. The method used in this research was quantitative research using correlational research approaches to find the relationship of learning motivation and academic achievement. The population in this study was all students in class XI SMK TKR Karsa Mulya Palangkaraya for second semester of academic year 2015/2016 with a total of as many as 57 students. Samples were taken with a sample or samples to be saturated where all the population used as a sample is about numbered at 57 students. Instruments motivation to learn before doing research conducted trials instrument in SMK 1 Palangkaraya with the number of respondents as many as 25 students. The technique of collecting data was using questionnaires and documentation of the average value of the first semester report cards of grade XI TKR. From the data normality test has showed that motivation to learn and student achievement have normal distribution.The results of the study authors obtained is a significant relationship between learning motivation and learning achievement of students in Class XI SMK TKR Karsa Mulya Palangkaraya at academic year 2015/2016. This is based on the calculation analysis of the correlation coefficient r obtained by the 0.48 price turned out to be located above the 5% significance level of 0.26, or 1% of 0.34. Moreover, it is known that the contribution of learning motivation on student achievement in class XI SMK TKR Karsa Mulya Palangkaraya 2015/2016 at academic year by 23%, while 77% is determined by other factors.